A Case of Hyperparathyroidism due to a Large Intrathyroid Parathyroid Adenoma with Recurrent Episodes of Acute Pancreatitis - Kazunori Kageyama; Noriko Ishigame; Aya Sugiyama; Akiko Igawa; Takashi Nishi; Satoko Morohashi; Hiroshi Kijima; Makoto Daimon (Case Reports in Endocrinology)
We report a case of a 66-year-old woman who developed hyperparathyroidism due to a large intrathyroid parathyroid adenoma with episodes of acute pancreatitis. She had previously been treated for acute pancreatitis twice. Serum calcium was 12.4 mg/dL, and intact parathyroid hormone was 253 pg/dL. Ultrasonography and computed tomography of the neck with contrast enhancement revealed a soft tissue mass (28 mm transverse diameter) within the left lobe of the thyroid. 99mTc-MIBI scintigraphy demonstrated focal accumulation due to increased radiotracer uptake in the left thyroid lobe. Left hemithyroidectomy was performed. Histopathology showed no signs of invasion, and this is consistent with parathyroid adenoma. Immunostaining was positive for expression of chromogranin A and parathyroid hormone. The patient had no episode of pancreatitis after the operation. In a patient with recurrent episodes of pancreatitis, the possibility of complication with hyperparathyroidism should be considered.